Case report: Thoughts on two cases of total anomalous pulmonary venous connection complicated with pulmonary artery hypertension - Yan, Ling; Zhou, Yaxin; Li, Dayan; Li, Lingli; Tang, Hong (Frontiers in Cardiovascular Medicine, 2023)
The two primary pathological alterations of total anomalous pulmonary venous connection (TAPVC), a rare cyanotic congenital heart disease (CHD), are right heart failure and pulmonary artery hypertension (PAH). The timing and prognosis of surgery depend on the level of pulmonary hypertension. Surgery will not be an option after Eisenmenger syndrome appears. In light of this, it is crucial to assess patients’ PAH. In order to aid in the following treatment of related types of diseases, this article studied and compared the echocardiographic features and disease development of one adult and one child TAPVC patients complicated with PAH.